"To Shave or Not to Shave": Pubic Hair Removal and Its Association with Relational and Sexual Satisfaction in Women and Men. Issue 7 (15th May 2019) - Enzlin, Paul; Bollen, Kaat; Prekatsounaki, Sofia; Hidalgo, Liesbeth; Aerts, Leen; Deprest, Jan
Abstract: Background: Pubic hair removal (PHR) is a widespread practice that entails certain health risks; however, there remains a lack of scientific information on the prevalence and antecedents of PHR, as well as on its association with sexual behavior and relational satisfaction. Aims: To explore women's and men's attitudes regarding PHR and their PHR practices and the associations with demographic, relational, and sexual characteristics. Methods: A total of 2, 687 men and 1, 735 women living in Flanders (the Northern part of Belgium) completed an online survey. Participants ranged in age from 15 to 60+ years; they self-identified as heterosexual, bisexual, or homosexual and reported various relationship statuses. Main Outcome Measures: Demographic items (ie, age, religion, partner relationship status), sexuality-related items (ie, sexual activity, sexual orientation, age at first intercourse, number of sexual partners), PHR items (ie, reasons, inclination to have or not have sex after PHR, perceived partner preferences, partner's PHR), and relationship satisfaction, assessed with the Maudsley Marital Questionnaire. Results: Fewer men (39.1%) than women (80.3%) reported (partially) removing their pubic hair. In both men and women, the practice was associated with age, sexual activity, relationship status, and partner's PHR practice and expectations. In men, sexual and relationship satisfaction were correlated with their partner's PHR practices and whether these were in line with the men's expectations. In women, sexual and relationship satisfaction were mostly correlated with whether both partner's expectations were met. Although both men and women reported that the reasons for PHR were related to their sexual experiences and to their partner's preference, only women reported that PHR was a way to enhance feelings of femininity. Finally, the reasons for not engaging in PHR were related to partner preferences and side effects. Conclusion: PHR is a widespread practice and seems strongly associated with personal, partner-related, sexual, and relational factors. Strategies to prevent men and women from being confronted with health risks should take all these factors into account.